A educação continuada na profissão contábil : um estudo de caso no CRC/SE - Araujo, Kleber Silva de (2008)
This dissertation aims to analyze the Program of Continuing Education in accountancy, implemented by Resolution 945/02 passed by the Federal Council of Accountants, based on the analyses of data collected from 2003 to 2005 by independent auditors working in the state of Sergipe. Although it has also considered quantitative aspects, this research is primarily qualitative, having adopted a historical-critical focus, according to a dialectical approach; it endeavors to understand facts globally and not in isolation, deprived of a context. Semi-structured interviews were made with the auditors and representatives of the Regional Council of Accountants of Sergipe State. With the results, it was possible to delineate the profile of the members of this profession as well as his/her views on the Program. We found out their dissatisfaction with both the events realized in Sergipe and the possibility that the Program might be extended to the remaining accountancy sectors. It lacks structure and competence alike for its development in the State. The key point is the meager number of courses being offered by training agents, which are highly valued in the fulfillment of professional norms.